Chlorophyllin exerts synergistic anti-tumor effect with gemcitabine in pancreatic cancer by inducing cuproptosis - Jiaqiang Ren; Tong Su; Jiachun Ding; Fan Chen; Jiantao Mo; Jie Li; Zheng Wang; Liang Han; Zheng Wu; Shuai Wu (Molecular Medicine)
Abstract Pancreatic cancer (PC) has high lethality due to multiple reasons, and its limited response to conventional chemotherapy like gemcitabine (GEM) is a non-negligible one. Therefore, our study introduces Chlorophyllin (CHL) as an effective therapeutic candidate to enhance the therapeutic efficacy of GEM. Our results demonstrate that the combination of CHL and GEM exhibits a significant synergistic anti-tumor effect by targeting multiple oncogenic processes in PC, including inhibiting cell proliferation, invasion, and migration, as well as inducing cell apoptosis. Further investigations of mechanism have revealed that CHL induces cuproptosis in PC cells through a multifaceted process, involving depleting cellular intracellular glutathione (GSH), increasing reactive oxygen species (ROS) levels, and subsequently upregulating the HSP70 protein in response to heightened oxidative stress. Additionally, CHL releases free Cu2+, binds to the Ferredoxin 1 (FDX1) protein, and ultimately leads to the oligomerization of Dihydrolipoamide S-Acetyltransferase (DLAT) proteins to amplify the copper toxicity within PC cells. Moreover, in vivo experiments have demonstrated that the combination of CHL and GEM effectively inhibits the growth of subcutaneously transplanted tumors while maintaining a favorable biosafety profile. In conclusion, our study identifies CHL as a potent enhancer of GEM’s anti-tumor effects in PC through the induction of cuproptosis, thus providing a novel therapeutic avenue for patients with PC.